A Study of Heat Recovery and Hydrogen Generation Systems for Methanol Engines - Sviatoslav Kryshtopa; Ruslans Smigins; Liudmyla Kryshtopa (Energies)
Biofuels are the most essential types of alternative fuels, which currently have significant potential to reduce CO2 emissions compared to fossil fuels. Methanol is a more efficient fuel than petrol due to its physicochemical properties, such as a higher latent heat of vaporization, research octane number, and heat of combustion of the fuel–air mixture. Also, biomethanol is cheaper than traditional petrol and diesel fuel for agricultural countries. The authors have proposed a new approach to improve the characteristics and efficiency of methanol diesel engines by using biomethanol mixed with hydrogen instead of pure biomethanol. Using a hydrogen–biomethanol mixture in modern engines is an effective method because hydrogen is a carbon-free, low-ignition, highest-flame-rate, high-octane fuel. A small quantity of hydrogen added to biomethanol and its combustion in an engine with a heat exchanger increases the combustion temperature and heat release, increases engine power, and reduces fuel consumption. This article presents experimental results of methanol combustion and a hydrogen-in-methanol mixture if hydrogen was retained due to the utilization of the heat of the exhaust gases. The tests were carried on a single-cylinder experimental engine with an injection of liquid methanol and gaseous hydrogen mixtures. The experiments showed that green hydrogen generated onboard the car due to the utilization of heat significantly reduced fuel costs of engines of vehicles and technological installations. It was established a hydrogen gaseous mixture addition of up to 5% by mass to methanol requires a corresponding change in the coefficient of excess air to λ = 1.25. Also, using an additional hydrogen mixture requires adjustment at the ignition moment in the direction of its decrease by 4–5 degrees of the engine crankshaft. Hydrogen gas mixture addition reduced methanol consumption, reaching a maximum reduction of 24%. The maximum increase in power was 30.5% based on experimental data. The reduction in the specified fuel consumption, obtained after experimental tests of the methanol research engine on the stand, can be implemented on the vehicle engines and technological installations equipped with an onboard heat recovery system. Such a system, due to the utilization of heat and the supply of additional hydrogen, can be implemented for engines that work on any alternative or traditional fuels.